Integrasi Nilai-Nilai Kearifan Lokal Guna Mengoptimalkan Project Penguatan Profil Pelajar Pancasila (P5) di SMPN 1 Kota Serang - Arry Rifaldi Juangga; Dwi Fitri Agustina Sukmana; Oki Pamungkas; Piska Permatasari; Ratna Sari Dewi; Lukman Hidayat (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This research delves into the integration of local wisdom values to enhance the project aimed at strengthening the Pancasila student profile in SMPN 1 Kota Serang. The study investigates the characteristics of Pancasila students, the application of the Pancasila student profile, challenges encountered, and the integration of local wisdom values from the Kota Serang region. The project's success is evaluated, along with its impact on students' national character, and the role of stakeholders is analyzed. The findings suggest that the incorporation of local wisdom values significantly bolsters students' national character and contributes to the overall success of the project. This research holds implications for the development of curricula, character education, and future similar projects, emphasizing the importance of recognizing and integrating local cultural values to foster a stronger sense of national identity among students.